Characterization of isovelocity extension of activated muscle: a Hill-type model for eccentric contractions and a method for parameter determination - Till, O.; Siebert, T.; Rode, C.; Blickhan, R. (Journal of Theoretical Biology, 2008)
Tension in eccentric contractions of skeletal muscles is expressed with a Hill-type model with a term containing a tension-velocity relation and a second term which is supposed to account for effects of contraction history. Based on experimental data (rat gastrocnemius medialis) a method is derived to uniquely characterize the tension-velocity relation in the first term. Also, a description of the second term is derived and its single additional parameter is determined. The model is tested in simulations. The experimental data used to characterize the model indicates that the slope of tension in the second phase of eccentric contractions is independent of muscle length.